Melquisedec, sacerdote de el elyon Uma exegese de Gênesis 14,18-20 - Silva, Célio (2006)
In this study, which is based on Gênesis 14,18-20, we discuss about Melchizedek, king of Salem and his god el elyon, whose priest he is (v.18). The text is post-exilic, being an insertion to the chapter 14, and reflects the history of Judah in the period of its restauration (6th to 4th centuries b.C.) at a time when the priesthood at Jerusalem gradually assumed a power which they had never had before in their history, because the high-priest became a civil authority. Then Melchizedek, who receives the tithe from Abram, is an image that evokes the power of Jerusalem cult in the Judahite society and their allegeable right to tithe and gifts from the people. But Melchizedek, used by a later text, belongs to traditions that were earlier than the exile of Judah; traditions according to them the king also used to play a priestly role as religious chief and Iahweh s manager (Psalm 110). Of course this twofold function was a kind of legitimation of estructures of power characterized by a social, politic and economic organization, which, in general aspects, fits to the concept of tributary mode of production. Thus all a discourse built upon the king and upon other ideological aspects like the Zion theology, was used to support the status quo. And the use of the symbolic universe of religion took part. In this reseach we sustain the hypothesis that el elyon is a compounded name which bears el, that corresponds to the supreme god of Canaanite pantheon (ugaritic ilu), who has as one of his attribute the fact that he begot heaven and earth (what fits his tradition in arcaic cosmogonic conceptions from the Near East); and elyon, who seems to hide some characteristics of other god, Ba al (Psalm 18,7-17). Thus we notice that Melchizedek s god s name is the syncretic combination of some characteristics of two great deities of Canaanite pantheon